Mild traumatic brain injury exacerbates Parkinson's disease induced hemeoxygenase-2 expression and brain pathology: Neuroprotective effects of co-administration of TiO2 nanowired mesenchymal stem cells and cerebrolysin - Sharma A.; Muresanu D.F.; Castellani R.J.; Nozari A.; Lafuente J.V.; Sahib S.; Tian Z.R.; Buzoianu A.D.; Patnaik R.; Wiklund L.; Sharma H.S. (My University, 2025)
Mild traumatic brain injury (mTBI) is one of the leading predisposing factors in the development of Parkinson's disease (PD). Mild or moderate TBI induces rapid production of tau protein and alpha synuclein (ASNC) in the cerebrospinal fluid (CSF) and in several brain areas. Enhanced tau-phosphorylation and ASNC alters the molecular machinery of the brain leading to PD pathology. Recent evidences show upregulation of constitutive isoform of hemeoxygenase (HO-2) in PD patients that correlates well with the brain pathology. mTBI alone induces profound upregulation of HO-2 immunoreactivity. Thus, it would be interesting to explore whether mTBI exacerbates PD pathology in relation to tau, ASNC and HO-2 expression. In addition, whether neurotrophic factors and stem cells known to reduce brain pathology in TBI could induce neuroprotection in PD following mTBI. In this review role of mesenchymal stem cells (MSCs) and cerebrolysin (CBL), a well-balanced composition of several neurotrophic factors and active peptide fragments using nanowired delivery in PD following mTBI is discussed based on our own investigation. Our results show that mTBI induces concussion exacerbates PD pathology and nanowired delivery of MSCs and CBL induces superior neuroprotection. This could be due to reduction in tau, ASNC and HO-2 expression in PD following mTBI, not reported earlier. The functional significance of our findings in relation to clinical strategies is discussed. © 2020 Elsevier B.V.